Trial and Participant Characteristics of a Home-Visiting Diabetes Intervention: The Together Overcoming Diabetes Study - Melissa L. Walls; Kelley J. Sittner; Gabby J. Gomez; Reagan E. Cole; Sylvie R. Perkins; Rachel I. Steinberg; Angie K. Forsberg; Emily E. Haroz; Allison Barlow (Journal of Diabetes Research)
Trial Registration: ClinicalTrials.gov identifier: NCT04734015